Effects of Different Oligosaccharides on Growth Performance and Intestinal Function in Broilers - Chang, Ling; Ding, Yanan; Wang, Yushi; Song, Zehe; Li, Fei; He, Xi; Zhang, Haihan (Frontiers in Veterinary Science, 2022)
Objective: This study was conducted to investigate the effects of different oligosaccharides on growth performance and intestinal function in broilers. Methods: A total of 360 1-day-old chickens were randomly divided into 5 groups and fed with a basal diet, basal diet supplemented with 50 mg / kg chlortetracycline (ANT), 3 g / kg isomalto-oligosaccharide (IMO), 3 g / kg raffinose oligosaccharide (RFO) and 30 mg / kg chitooligosaccharide (COS). The experiment lasted for 56 days, with 1–28 days as the starter phase and 29–56 days as the grower phase. Results: The results showed that dietary supplementation with RFO and COS significantly improved average daily gain (ADG) and average daily feed intake (ADFI) (P<0.05). Relative to the control group, diets supplemented with oligosaccharide dramatically increased the level of serum IgM (RFO, COS), T-SOD (COS), GSH-Px (IMO and RFO) and the expression of ZO-1(IMO) and Claudin-1 (RFO) (P < 0.05). Adding antibiotics or oligosaccharides to the diet could remarkedly increase the villus height and villus height (VH)/crypt depth (CD) ratio of each group (P<0.05). Through the ileum α Diversity analysis and comparison of OTU number in each group showed that the microbial richness of IMO group increased in the starter phase, and that of RFO and CSO group increased in the grower phase. Additionally, compared with the control group, IMO supplementation increased the level of ileum sIgA (P<0.05) and the content of valeric acid (P<0.05) in the cecum. Conclusions: In summary, the addition of oligosaccharides in diet can improve the immune function, antioxidant capacity and improve intestinal health of broilers.